Answer:
32
Step-by-step explanation:
substitute the given values of a, b and c into the expression:
b² - 2ac = 4² - (2 x 4 x -2)
= 16 - (-16)
= 16 + 16
= 32
The function’s value when x = −1 will be C. g(−1) = 1.
<h3>How to calculate the value of the function?</h3>
It should be noted that that a function is simply used to show the relationship that exists between the variables.
There's a 2-column table with 5 rows. The first column is labeled g of x with entries negative 3, negative 2, 0, 2, 3. The second column is labeled f of x with entries.
The. function is x³ + 6x² + 12x + 8.
= x³ + 6x² + 12x + 8.
= (-1)³ + 6(-1)² + 12(-1) + 8
= -1 + 6 - 12 + 8
= 1
Therefore, the correct option is C.
Learn more about functions on:
brainly.com/question/25638609
#SPJ1
Answer:63
Step-by-step explanation:
we know that two similar triangles will have ratio corresponding side is same.
ratio triangle 1 is 75m^2.
and triangle 2 is 12m^2.
![75:12=\frac{75}{12} =\frac{25}{4} .](https://tex.z-dn.net/?f=%2075%3A12%3D%5Cfrac%7B75%7D%7B12%7D%20%3D%5Cfrac%7B25%7D%7B4%7D%20.%20)
so we have ratio of area
.
ratio of perimeter will be
.
from these perimeter ratio also
.